Stratification-Based Investigation of Adjunctive Brimonidine or Timolol to a Prostaglandin Analogue in Japanese Patients with Normal-Tension Glaucoma - Yoshikawa K (Dove Medical Press, 2021)
Keiji Yoshikawa,1 Shiro Mizoue,2,3 Koji Nitta,4 Hiroshi Onishi,5 Masaharu Ikeda,5 Akemi Mizuno,5 Kaori Kawazoe,5 Yoshiyuki Tamada,5 Ryuji Takeda,6 Shun Matsumoto7 1Yoshikawa Eye Clinic, Tokyo, Japan; 2Ehime University Hospital, Toon, Ehime, Japan; 3Minami-Matsuyama Hospital, Matsuyama, Ehime, Japan; 4Fukui-ken Saiseikai Hospital, Fukui, Japan; 5Senju Pharmaceutical Co. Ltd., Hyogo, Japan; 6Kansai University of Welfare Sciences, Osaka, Japan; 7Ideta Eye Hospital, Kumamoto, JapanCorrespondence: Keiji YoshikawaYoshikawa Eye Clinic, 1-3-1 Nakamachi, Machida, Tokyo, 194-0021, JapanTel +81-42-739-0781Fax +81-42-739-0782Email mayokasyg51@galaxy.ocn.ne.jpPurpose: We previously investigated the efficacy and safety of adding 0.1% brimonidine (Brim) or 0.5% timolol (Tim) to prostaglandin analogue (PGA) monotherapy to treat patients with normal-tension glaucoma (NTG) with intraocular pressure (IOP) of ≤ 16 mmHg. Herein, we describe an additional post-hoc stratifying analysis of the possible differences in the effect of IOP-lowering and pulse rate (PR) after adjunctive Brim or Tim to PGA.Patients and Methods: This study included 128 subjects. Patients with NTG treated with PGA were stratified based on their baseline IOP. The changes in IOP from baseline and the effect of patient factors on IOP changes were investigated. Patients were stratified by age for investigation of their PR and blood pressure (BP). The change and the effect of patient factors on PR and BP were investigated.Results: After stratification analysis, in 52 eyes treated with Brim and 61 eyes with Tim with baseline IOP 12 ≤ IOP ≤ 16 mmHg, both eye drops lowered IOP significantly (P < 0.0001), and the IOP-lowering efficacy of Brim was non-inferior to that of Tim. However, in 9 Brim- and 6 Tim-treated eyes with baseline IOP of < 12 mmHg, no statistically significant decrease in IOP was evident with either eye drop. In the Tim group, PR decreased significantly (P < 0.05) after stratification by age.Conclusion: The IOP-lowering efficacy of Brim was non-inferior to that of Tim after stratification by baseline IOP (12 ≤ IOP ≤ 16 mmHg). The discrepancy in the IOP-lowering effects of Brim and Tim observed in the previous study was thought to be related to enrolled subjects with low baseline IOP. PR decreased significantly in the Tim group even after age stratification. PR should be considered when selecting β-blockers for glaucoma treatment.Keywords: adjunctive therapy, brimonidine, intraocular pressure reduction, post-hoc analysis, pulse rate, timolol